2015
DOI: 10.1093/ejcts/ezv069
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve disease and ascending aortic aneurysm: should an aortic root replacement be mandatory?

Abstract: In patients with BAV disease, ascending aorta aneurysm and moderate dilatation of the root, the significat reduction of CPB and cross-clamp times, the stability of the residual root at long term and the low risk of adverse aortic events associated with SAAR compared with the Bentall procedure have led us to consider the isolated aortic valve replacement with supracoronary aorta replacement an alternative strategy to the Bentall procedure, especially in high-risk and older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
1
22
1
2
Order By: Relevance
“…3,18 A recent investigation reported no significant change in the sinus segment less than 40 mm and no difference in survival in patients with BAV between those in whom the sinus segment is removed (Bentall) and those in whom the sinus segment is retained (AVRSCAAR). 11 In this study, analysis of the sinus segment showed a significant decrease in size in patients with a preoperative sinus segment greater than 40 mm. However, this study did not account for time bias.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…3,18 A recent investigation reported no significant change in the sinus segment less than 40 mm and no difference in survival in patients with BAV between those in whom the sinus segment is removed (Bentall) and those in whom the sinus segment is retained (AVRSCAAR). 11 In this study, analysis of the sinus segment showed a significant decrease in size in patients with a preoperative sinus segment greater than 40 mm. However, this study did not account for time bias.…”
Section: Discussionmentioning
confidence: 49%
“…In patients with critical aortic valve disease and ascending aortic aneurysm, the management of the SOV segment for patients with a moderately dilated aortic root remains unresolved. Multiple studies have advocated AVR-SCAAR as a treatment, thereby preserving the intact moderately dilated sinus segment and coronary ostia, 10,11 whereas others suggest removal of the sinus segment and a Bentall root replacement procedure. 12,13 However, most investigations have limited their analysis to the retention or replacement of the sinus segment of known congenital BAV aortopathies.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the threshold for resection the aorta in case of a nondiseased bicuspid valve was 55% at 50 mm and 23% at 45 mm, whereas a diseased valve lowers the threshold to 45 mm in 61% and to 40 mm in 29% of the surgeons' decisions. However, the good results reported in the current article and others [12][13][14][15] for the RS approach advocate for a more liberal treatment in elective patients.…”
Section: Discussionmentioning
confidence: 59%
“…Studies from the University of Virginia, University of Toronto, Northwestern University, and, most recently, University of Udine, focusing on bicuspid valves, presented similarly favorable results and confirm the safety of the RS approach found in the present study. [12][13][14][15] Even by extending the surgical approach close to or into the arch portion (with an open distal anastomosis and the need for DHCA), the postoperative outcomes remained favorable, with a mortality of 0%. Because of the more complex operative approach, a slightly higher incidence of prolonged ventilation (5%-7% vs 3%-4%), renal failure (4% vs 2%-3%), and postoperative need for antibiotic treatment (infection 3%-5% vs 2%-3%) were found.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention depends on the clinical presentation [20,21]. Valve repair or replacement for valvular lesions, Bentall procedure for root and ascending aortic dilatation and isolated replacement or repair of the ascending aortas.…”
Section: Discussionmentioning
confidence: 99%